The Crucial Role of Innovation in Driving Organizational Growth, Success, and Sustainability - Eduard Hotman Purba; Haryanto Haryanto; Andri Cahyo Purnomo (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Innovation has become a fundamental element in industrial development and organizational advancement because it influences competitiveness, market coordination, and long-term organizational sustainability. Innovation is integrated into various aspects of human activities through product development, managerial approaches, operational methods, and organizational transformation processes. This study aims to examine the crucial role of innovation in driving organizational growth, success, and sustainability through a qualitative conceptual approach and literature review method. The analysis demonstrates that innovation is not limited to creativity or the generation of new ideas but involves systematic processes of transforming ideas into applicable solutions that create organizational value. The findings indicate that innovation capability contributes to organizational development by strengthening adaptability, improving competitiveness, supporting strategic renewal, and enabling organizations to respond effectively to changing market conditions. Innovation also functions as a strategic mechanism that connects creativity, knowledge management, technological advancement, and sustainable organizational performance. This study highlights that innovation should be managed as a continuous organizational capability rather than a temporary activity to ensure long-term success and resilience in dynamic global environments.